Determinants of long-term fatigue in breast cancer survivors: results of a prospective patient cohort study - Schmidt, Martina E.; Chang-Claude, Jenny; Seibold, Petra; Vrieling, Alina; Heinz, Judith; Flesch-Janys, Dieter; Steindorf, Karen (Psycho-oncology (Chichester, England), 2015)
Objective Fatigue is among the most distressing symptoms across the breast cancer continuum. However, little is known about the factors contributing to long‐term persisting fatigue. Therefore, we explored determinants of long‐term physical, affective, and cognitive fatigue in a prospective cohort of breast cancer patients. Methods Breast cancer patients recruited in a population‐based case–control study (MARIE study) provided comprehensive data on sociodemographics, lifestyle, and preexisting medical conditions. At follow‐up (median 6.3 years post‐diagnosis, MARIEplus), disease‐free cancer survivors (N = 1928) reported current fatigue using a validated multidimensional questionnaire. Additionally, survivors retrospectively rated their fatigue levels before diagnosis, during the treatment phase, and 1 year post‐surgery. Linear regression analyses were performed. Results As major determinants of long‐term physical, affective, and cognitive fatigue, multiple regression analyses revealed preexisting psychological or depressive disorders, migraine, analgesic use, peripheral arterial obstructive disease (PAOD), and arthritis. A physically inactive lifestyle and obesity were associated with persisting physical fatigue. Aromatase inhibitors were also associated with long‐term fatigue, especially cognitive fatigue. Chemotherapy and, to a lower extent, radiotherapy were major contributors to the development of fatigue during the treatment phase, yet were not associated with long‐term fatigue. Conclusions Although the development of fatigue in breast cancer patients seems largely impacted by cancer therapy, for the long‐term persistence of fatigue, preexisting medical or psychological conditions related to depression or pain and lifestyle factors appear to be more relevant. Physicians, psycho‐oncologists, and researchers may need to distinguish between acute fatigue during therapy and long‐term persisting fatigue with regard to its pathophysiology and treatment. Copyright © 2014 John Wiley & Sons, Ltd.